Plasmonic Scissors for Molecular Design. Issue 44 (13th September 2013) - Sun, Mengtao; Zhang , Zhenglong; Kim, Zee Hwan; Zheng, Hairong; Xu, Hongxing
Abstract Heterogeneous catalysts play an important role in surface catalytic reactions, but selective bond breaking and control of reaction products in catalytic processes remain significant challenges. High‐vacuum tip‐enhanced Raman spectroscopy (HV‐TERS) is one of the best candidates to realize surface catalytic reactions. Herein, HV‐TERS was employed in a new method to control dissociation by using hot electrons, generated from plasmon decay, as plasmonic scissors. In this method, the NN bond in 4, 4′‐dimercaptoazobenzene was selectively dissociated by plasmonic scissors, and the reaction products formed from the radical fragment (SC6H5N) were controlled by varying the pH value. Under acidic conditions, p‐aminothiophenol was produced from the radical fragment by attachment of hydrogen ions, whereas under alkaline conditions, 4‐nitrobenzenethiol was obtained by attachment of oxygen ions to the substrate.